2021
DOI: 10.1111/1755-0998.13486
|View full text |Cite
|
Sign up to set email alerts
|

The potential of aquatic bloodfeeding and nonbloodfeeding leeches as a tool for iDNA characterisation

Abstract: Leeches (Hirudinea sensu Tessler, de Carle, et al., 2018) are found on all continents except Antarctica (Sket & Trontelj, 2008). There are around 900 known leech species (Magalhães et al., 2021) and these have varying and important roles in food webs; they can be ectoparasitic (or, on occasion, endoparasitic: Mann & Tyler, 1963), predatory, intermediate and final hosts for parasites (Sawyer, 1986), vectors of hemogregarine and trypanosome blood para-

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 102 publications
0
9
0
Order By: Relevance
“…While eDNA-based approaches may allow for relatively rapid sampling, it often requires weeks or months of laboratory work, and species identifications can be limited by primer biases and DNA reference databases. Moreover, only freshwater eDNA (Ushio et al, 2018) and iDNA from bulk arthropod samples and leeches (Ji et al, 2022;Lynggaard et al, 2019;Lynggaard, Oceguera-Figueroa, et al, 2022) have been found applicable for bird detection.…”
Section: Vertebrate Taxa Detected Using Airborne Ednamentioning
confidence: 99%
“…While eDNA-based approaches may allow for relatively rapid sampling, it often requires weeks or months of laboratory work, and species identifications can be limited by primer biases and DNA reference databases. Moreover, only freshwater eDNA (Ushio et al, 2018) and iDNA from bulk arthropod samples and leeches (Ji et al, 2022;Lynggaard et al, 2019;Lynggaard, Oceguera-Figueroa, et al, 2022) have been found applicable for bird detection.…”
Section: Vertebrate Taxa Detected Using Airborne Ednamentioning
confidence: 99%
“…According to their diet, leeches are divided into 3 groups: carnivorous, blood-sucking and liquid-sucking groups (Sawyer, 1986;Lynggaard et al, 2022). The leeches we studied also belong to the above groups.…”
Section: Feeding Of Leeches and Gastropodsmentioning
confidence: 99%
“…Like eDNA, invertebrate-derived DNA (iDNA) often allows for the detection of vertebrate mtDNA. Leeches (e.g., Drinkwater, Jucker, et al, 2021;Lynggaard, Oceguera-Figueroa, et al, 2022;Schnell et al, 2012Schnell et al, , 2015Schnell et al, , 2018, carrion flies (e.g., Calvignac-Spencer, Merkel, et al, 2013;Gogarten et al, 2020;Hoffmann et al, 2018;Rodgers et al, 2017), sandflies (Kocher et al, 2017;Massey et al, 2022), mosquitos (e.g., Kocher et al, 2017;Massey et al, 2022), and dung beetles (Drinkwater, Williamson, et al, 2021) have all been successfully used in metabarcoding studies targeting mtDNA.…”
Section: Introductionmentioning
confidence: 99%